2017
DOI: 10.1038/s41598-017-13092-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of putative colorectal cancer biomarker candidates in serum extracellular vesicles by targeted proteomics

Abstract: At the moment, there is no sensitive clinical test for detecting early-stage colorectal cancer (CRC). Target proteomics has enabled high-throughput verification of hundreds of biomarker candidate proteins. Using this technology, we verified 725 previously reported CRC biomarker candidate proteins that are functionally correlated with CRC in extracellular vesicles (EVs) from patients. Of these, 356 proteins were quantified, and 34 peptides (22 proteins) showed significant differences in the serum EVs between he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 32 publications
(33 reference statements)
0
50
0
1
Order By: Relevance
“…An additional separation step of the extracted EV proteins is usually performed before MS analysis using either gel electrophoresis [ 125 ] or LC [ 126 , 127 ] to facilitate proteomic analysis removing the contaminants in the sample. Moreover, specific separation methods for the study of post-translational modifications of EV proteins have also been applied in many proteomic studies.…”
Section: Proteomic Methodsmentioning
confidence: 99%
“…An additional separation step of the extracted EV proteins is usually performed before MS analysis using either gel electrophoresis [ 125 ] or LC [ 126 , 127 ] to facilitate proteomic analysis removing the contaminants in the sample. Moreover, specific separation methods for the study of post-translational modifications of EV proteins have also been applied in many proteomic studies.…”
Section: Proteomic Methodsmentioning
confidence: 99%
“…In cancer EV studies, SRM/MRM is one of the promising strategies to evaluate potential biomarkers using large scale clinical samples. Shiromizu et al examined serum‐EVs from healthy donors and patients with colorectal cancer (CRC) using SRM/MRM analysis . Among the 356 quantified proteins (stable isotope‐peptide labeled), 34 peptides from 22 proteins showed a significant difference between healthy and CRC patients .…”
Section: Cancer Ev Proteomics—methods and Analysesmentioning
confidence: 99%
“…Shiromizu et al examined serum‐EVs from healthy donors and patients with colorectal cancer (CRC) using SRM/MRM analysis . Among the 356 quantified proteins (stable isotope‐peptide labeled), 34 peptides from 22 proteins showed a significant difference between healthy and CRC patients . Further data analysis identified that annexins A3, A4, and A11 peptides may serve as promising biomarkers for early CRC detection …”
Section: Cancer Ev Proteomics—methods and Analysesmentioning
confidence: 99%
“…Not only ascites, but also serum exosome can be a good diagnostic marker. Annexin proteins, and tspan 1 from the serum exosome are suggested colon cancer diagnostic markers [35,117]. However, most cancer derived exosomes, as mentioned in breast and lung cancer derived exosomes as above, contain a lot more annexin and tetraspanin proteins than normal control derived exosome.…”
Section: Other Cancersmentioning
confidence: 99%